2016
DOI: 10.1108/jmtm-07-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

5S impact on safety climate of manufacturing workers

Abstract: Purpose – 5S is a commonly used Lean tool that focusses on creating an organized work environment, but the effects of 5S on safety climate are not as well studied. The purpose of this paper is to determine the impact of a 5S event on safety climate. Design/methodology/approach – This pre-test post-test study examines the effect of implementing 5S on safety climate of the packaging area of a manufacturing plant. Two groups of employees (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…5S practices is very important because it can help organizations to reduce costs by maximizing process efficiency, effectiveness and performance through the establishment and maintenance of a high-quality, clean working environment (Suárez-Barraza and Ramis-Pujol, 2012; Hirano, 1995;Ho, 1999;Liker, 2004;Liker and Hoseus, 2008). Therefore, study by Srinivasan, et al (2016) show that two important aspects of safety climate (management commitment and involvement) can be significantly, positively influenced by successful 5S events, which may translate to improved safety overall. Gupta and Chandna (2020) analyze the implementation of 5S in a scientific equipment manufacturing company and found that the organization become progressively beneficial and increasingly productive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5S practices is very important because it can help organizations to reduce costs by maximizing process efficiency, effectiveness and performance through the establishment and maintenance of a high-quality, clean working environment (Suárez-Barraza and Ramis-Pujol, 2012; Hirano, 1995;Ho, 1999;Liker, 2004;Liker and Hoseus, 2008). Therefore, study by Srinivasan, et al (2016) show that two important aspects of safety climate (management commitment and involvement) can be significantly, positively influenced by successful 5S events, which may translate to improved safety overall. Gupta and Chandna (2020) analyze the implementation of 5S in a scientific equipment manufacturing company and found that the organization become progressively beneficial and increasingly productive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason is that in high demand periods company always focuses on the case, the plant manager is overwhelmed and is more concerned about meeting customer delivery times rather than maintaining an orderly plant [25]. If the problems of 5S were not well conducted, safety risks may cause injury [26]. The current research aimed at assessing the effects of a 5S event on safety in a production environment by comparing all employees involved in batch processing.…”
Section: Lack On 5s Activitiesmentioning
confidence: 99%
“…Moreover, Khamis et al (2009) demonstrated the use of 5S checklist for better housekeeping in terms of preserving health, safety and environment in a manufacturing firm. Further, by implementing 5S principles, the levels of quality, lead time, and cost reduction can be improved (Gadzik, 2009;Chowdary and George, 2012;Kumar et al, 2014;Srinivasan et al, 2016;Chowdary et al, 2016;Setianto and Haddud, 2016;Sajan et al, 2017;Chowdary et al, 2018).…”
Section: Lean Tools and Applicationsmentioning
confidence: 99%
“…• For reduction of process wastes, various LM tools such as 5S, PS, TPM, super market concept, setup time reduction, etc. are implemented widely across variety of industries (Abdullah, 2003;Gadzik, 2009;Monden, 2012;Srinivasan et al, 2016;Bevilacqua et al, 2017;Chowdary et al, 2018).…”
Section: Survey On Application Of Lm Tools To Steel Industrymentioning
confidence: 99%
See 1 more Smart Citation